The forms of international specialization and ensuing economic flows. Case study on the cocoa products - Elina BENEA-POPUȘOI (Academy of Economic Studies of Moldova, 2021)
The development of the world economy is primarily determined by the process of international specialization. The production of the specialized economic branches is usually distinguished by high quality; therefore, it is demanded in the world market. Since each country specializes in the production of certain types of products and their volume exceeds the demand in the domestic market, the need to export them emerges. International specialization aims to adapt the national economic potential, the domestic economy to the requirements of the world market. Hence as result of such specialization, international trade flows take place, that strengthen the economic interdependencies between countries. The global chocolate market size was valued at USD 130.56 billion and is considerably growing. The cocoa beans are the essential ingredient for chocolate, cocoa products and a wide range of other food products. Global cocoa production is expected to reach 4.8 million tons in the 2020/2021 crop year. Lately, the price of cocoa has been well over two U.S. dollars per kilogram.